Metabolic engineering of Yarrowia lipolytica for enhanced microbial production of medium-chain α, ω-diols from alkanes via CRISPR-Cas9 mediated pathway optimization and P450 alkane monooxygenase overexpression - Kim, Ye Chan; Hwan Choi, Won Yoon; Kim, Eun-Jung; Kim, Byung‐Gee; Yun, Hyungdon (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMedium- to long-chain α, ω-diols are valuable building blocks for polyesters and polyurethanes, yet their microbial synthesis from inexpensive alkane feedstocks remains largely undeveloped. The oleaginous yeast Yarrowia lipolytica offers advantages over bacterial systems such as Escherichia coli for alkane conversion due to its inherent capacity to metabolize hydrophobic substrates.MethodsTo enable de novo α, ω-diol production from alkanes, we used CRISPR-Cas9 to delete ten genes involved in fatty alcohol oxidation (including FADH, ADH1 -8, and FAO1) and four genes linked to fatty aldehyde oxidation (FALDH1 -4). This generated the strain YALI17, with reduced over-oxidation activity. Further metabolic enhancement was achieved by overexpressing alkane hydroxylase genes, particularly ALK1. Fermentation performance was evaluated under controlled pH conditions using n-dodecane as the substrate.ResultsThe engineered strain YALI17 produced 1,12-dodecanediol at 0.72 mM from 50 mM n-dodecane –a 14-fold increase relative to the parental strain. ALK1 overexpression in YALI17 further raised production to 1.45 mM, and automated pH-controlled biotransformation achieved 3.2 mM.DiscussionThis study demonstrates the first successful biotransformation of medium- to long-chain α, ω-diols directly from alkanes in yeast. The rational pathway design and oxidation-pathway blocking highlight Y. lipolytica as a promising cell factory for alkane-based biomanufacturing and lay the groundwork for sustainable production of high-value diol precursors through targeted metabolic engineering.